1984
DOI: 10.1113/jphysiol.1984.sp015241
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly activating hydrogen ion currents in perfused neurones of the snail, Lymnaea stagnalis.

Abstract: SUMMARY1. Cells from the circumoesophageal nerve ring of the pond snail Lymnaea 8tagnali8 were internally perfused with solutions containing Cs aspartate, EGTA and pH buffers. Time-dependent, voltage-dependent 'residual' outward currents were observed at positive potentials. They were found to be carried largely by H+.2. The outward H+ currents were reduced by high internal pH, low external pH, external Cd2+ and 4-aminopyridine. External tetraethylammonium ions reduced the H+ currents but had a more effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
246
1
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(274 citation statements)
references
References 33 publications
26
246
1
1
Order By: Relevance
“…Yet very little inward current has been observed through H+ channels (Barish and Baud, 1984;Byerly et al, 1984;Decoursey, 199 1). Hf influx through other channel types may also be insufficient for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet very little inward current has been observed through H+ channels (Barish and Baud, 1984;Byerly et al, 1984;Decoursey, 199 1). Hf influx through other channel types may also be insufficient for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…One often suggested possibility involves hydrogen ions entering neurons directly either through GLU channels, hydrogen ion channels, or other voltage-activated channels (Thomas and Meech, 1982;Mozhayeva and Naumov, 1983;Barish and Baud, 1984;Byerly et al, 1984;Chesler and Chan, 1988). Yet very little inward current has been observed through H+ channels (Barish and Baud, 1984;Byerly et al, 1984;Decoursey, 199 1).…”
Section: Discussionmentioning
confidence: 99%
“…The strong shift is not explained by simple shielding of surface charges, since Ca 2+ at the same concentration failed to produce the same effect as Ba 2+ . There are precedents for specific divalent cations shifting the activation range of voltage-dependent ion channels by amounts exceeding those predicted by simple shielding of surface charges (e.g., Byerly et al, 1984), but such an effect of Ba 2+ on K + channels is novel (for review see Yellen, 1987), and the mechanism for these interactions is unknown.…”
Section: Properties Of I Kxmentioning
confidence: 99%
“…A modified form of the constant-field equation as used by Brown et al (1983) can describe the data but it is necessary to incorporate a correction factor for positive potentials. Other authors have reported the observed currents at positive potentials to be carried not only by Ca2+ but also by Cs+ passing through Ca2+ channels (Fenwick et al 1982) or by H+ through distinct channels (Byerly, Meech & Moody, 1984b). The term D in eqn (7) would account for all these contaminating outward currents.…”
Section: Activation Of the Ca2+ Currentmentioning
confidence: 99%